Electrolyte soaking-resistant coating high-temperature-resistant diaphragm and preparation method thereof

By coating high-temperature resistant fiber polymer slurry on the lithium-ion battery separator, the stability and safety of the separator in high temperature and electrolyte immersion are solved, and the heat resistance of the separator and electrolyte immersion stability are improved, thereby enhancing the safety of the battery.

CN119742540APending Publication Date: 2025-04-01HENAN HUIQIANG NEW ENERGY MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411800632.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators have stability and safety problems in high temperature and electrolyte organic solvent soaking, which can easily lead to problems such as black leakage of the electrode sheet, fluffy battery cell and thermal runaway.

Method used

By coating high-temperature resistant fiber polymer slurry, including PPS fibers, inorganic ceramic powders and PI polymers on the polyolefin separator, a dense coating is formed using microgravure transfer coating technology to improve the high-temperature resistance and electrolyte immersion properties of the separator.

Benefits of technology

It significantly improves the heat resistance of the diaphragm and the electrolyte immersion stability, prevents the electrode sheet from leaking black and the battery cell fluffy, and enhances the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742540A_ABST
    Figure CN119742540A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte soaking-resistant coating high-temperature-resistant diaphragm and a preparation method thereof.The high-temperature-resistant diaphragm comprises a diaphragm substrate and a diaphragm coating, the diaphragm coating is formed by coating high-temperature-resistant fiber polymer slurry, and the high-temperature-resistant fiber polymer slurry comprises, by mass, 2-5 parts of PPS fibers and 8-15 parts of PI polymers. The coating comprises the following components in parts by weight: 65-80 parts of inorganic ceramic powder, 4-8 parts of a CMC thickener, 3-6 parts of an acrylic resin adhesive and 0.1-0.5 part of a sodium polycarboxylate surfactant. The fiber polymer is coated on the basis of the polyolefin diaphragm, so that the high-temperature resistance of the diaphragm and the stability of the diaphragm in an electrolyte can be improved, the stability of the diaphragm can be maintained in a battery cell baking stage to prevent black leakage of a pole piece, and the cohesiveness of a coating and the pole piece after liquid injection of the battery cell can be improved; the swelling phenomenon caused by thermal runaway due to fluffy battery cells is prevented, and the safety of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, in particular to a high temperature resistant diaphragm coated with electrolyte immersion resistance and a preparation method thereof. Background Art

[0002] Lithium battery separator is one of the four key materials of lithium-ion battery. The performance of separator determines the interface structure and internal resistance of the battery, and directly affects the battery's capacity, cycle and safety performance. Excellent separator plays an important role in improving the comprehensive performance of the battery. The important use of separator is to separate the positive and negative electrodes of the battery to prevent the two electrodes from contacting and short-circuiting. In addition, it also has the function of allowing electrolyte ions to pass through. In addition, since the electrolyte is an organic solvent, the separator must also have the performance of being resistant to organic solvents.

[0003] The electrolyte is one of the four key materials of lithium-ion batteries: positive electrode, negative electrode, separator, and electrolyte. It is known as the blood of lithium-ion batteries. It conducts electrons between the positive and negative electrodes in the battery and is the guarantee for lithium-ion batteries to obtain advantages such as high voltage and high specific energy. The electrolyte is generally made of high-purity organic solvents, electrolyte lithium salts, necessary additives and other raw materials, prepared under certain conditions and in a certain proportion. Important electrolytes used include lithium perchlorate, lithium hexafluorophosphate, etc.

[0004] The electrolyte is filled inside the battery shell, and the positive and negative electrodes and diaphragms of the lithium battery are immersed in it. On the one hand, the electrolyte supplies some active lithium ions and is used as conductive ions during the charging and discharging process. On the other hand, the electrolyte supplies ion channels, or carriers, so that lithium ions can move freely in it. Since the electrolyte is an organic solvent, which is different from the aqueous solution system, the safety performance of the diaphragm after the electrolyte is injected into the battery cell is crucial. How the diaphragm maintains good ion permeability, small internal resistance, good lyophilicity, strong liquid retention, good chemical stability, especially the material resistant to organic solvents of the electrolyte, the diaphragm has become a very critical factor. Summary of the invention

[0005] In view of the deficiencies of the above-mentioned prior art, the present invention provides a high-temperature resistant diaphragm coated with an electrolyte immersion resistance and a preparation method thereof. By coating a fiber polymer on the basis of a polyolefin diaphragm, not only the high-temperature resistance of the diaphragm can be improved, but also the stability of the coating layer maintained during immersion in an organic solvent of an electrolyte can be improved. Not only can the stability of the diaphragm be maintained during the baking stage of the battery cell to prevent the electrode from leaking black, but also the adhesion between the coating and the electrode layer after the battery cell is injected can be improved to prevent the battery cell from becoming fluffy, causing thermal runaway and resulting in bulging, thereby greatly improving the safety of the battery.

[0006] The technical solution provided by the present invention is: an electrolyte immersion-resistant high-temperature resistant diaphragm, comprising a diaphragm substrate and a diaphragm coating, wherein the diaphragm coating is formed by coating a high-temperature resistant fiber polymer slurry, and the high-temperature resistant fiber polymer slurry comprises the following components in parts by mass: 2-5 parts of PPS fiber, 8-15 parts of PI polymer, 65-80 parts of inorganic ceramic powder, 4-8 parts of CMC thickener, 3-6 parts of acrylic resin glue, and 0.1-0.5 parts of polycarboxylic acid sodium salt surfactant. The high-temperature resistant fiber polymer slurry also includes a solvent, which is ultrapure water. The solid content of the slurry of the diaphragm coating is 32-45%.

[0007] Furthermore, the high temperature resistant fiber polymer slurry is transferred and coated on both sides of the diaphragm substrate by a micro-gravure roller.

[0008] Furthermore, the high temperature resistant fiber polymer slurry includes the following components by mass: 4.8 parts of PPS fiber, 14.5 parts of PI polymer, 68 parts of inorganic ceramic powder, 7 parts of CMC thickener, 5.5 parts of acrylic resin glue, and 0.2 parts of polycarboxylic acid sodium salt surfactant.

[0009] Furthermore, the PPS fiber is a short fiber with a particle size D50 less than 12 um, the PI polymer is a para- or meta-polyimide emulsion, and the inorganic ceramic powder is one of alumina or boehmite.

[0010] Another technical solution provided by the present invention is a method for preparing a high temperature resistant diaphragm resistant to electrolyte immersion coating, comprising the following steps:

[0011] S1: CMC thickener, inorganic ceramic powder and PPS fiber are pre-mixed and dispersed;

[0012] S2: After premixing and dispersion, it is subjected to high-speed grinding and shearing to reach the required solution particle size;

[0013] S3: adding PI polymer to the ground solution and mixing at high speed;

[0014] S4: Add acrylic resin glue and continue mixing at low speed;

[0015] S5: adding a polycarboxylate sodium salt surfactant and mixing at a low speed to form a coating slurry;

[0016] S6: Transfer coating, drying and rolling into semi-finished products through micro-gravure coating equipment;

[0017] S7: Cut the battery cells into finished products according to their size requirements using a slitting machine.

[0018] Furthermore, the solvent for preliminary premixing and dispersion in step S1 is deionized ultrapure water, which is premixed and dispersed in a premixing tank, the premixing tank has an orbital speed of 20-30 rpm and an autorotation speed of 1000-3000 rpm, the stirring tank for high-speed dispersion in step S3 has an orbital speed of 25-40 rpm and an autorotation speed of 2000-3000 rpm, the autorotation speed of low-speed mixing in step S4 is 100-300 rpm, and the oven drying temperature in step S6 is 50-80°C, and the temperature is set in a gradient manner of low to high.

[0019] Furthermore, in step S7, the speed of the slitting machine is controlled to be 60-150 m / min, the unwinding tension of the slitting machine is 20-40 N, the winding tension is 10-20 N, and the winding taper is gradually reduced at a rate of 10%.

[0020] Furthermore, the coating thickness of the electrolyte resistant immersion coated high temperature resistant diaphragm is controlled to be 2-4um, and the coating surface density is controlled to be 3-8g / m 2 , the width of semi-finished film is 0.5-1.5m.

[0021] Furthermore, in step S5, the coating slurry has a viscosity of 20-200 mps, and a particle size D50 of 0.5-2 um.

[0022] Further, the specific steps are as follows:

[0023] S1: Prepare 6.2 parts of CMC thickener, 73 parts of inorganic ceramic powder, 3.2 parts of PPS fiber, add 185 parts of ultrapure water according to the liquid content, add to the premixing tank, premix and disperse for 120 minutes, revolve at 25 rpm, and rotate at 1800 rpm;

[0024] S2: The premixed and dispersed solution enters the grinding and shearing process through the pump speed, the grinding speed is 800rmp, the pump speed of the grinder is 1s / time, and the ground solution enters the stirring tank;

[0025] S3: grind the solution into a stirring tank, add 12 parts of PI polymer, and perform high-speed dispersion. The stirring tank for high-speed dispersion revolves at 30 rpm and rotates at 2800 rpm for 60 min.

[0026] S4: 5.3 parts of acrylic resin glue is added to the stirring tank and dispersed at a low speed. The stirring tank rotates at 200 rpm for 30 min.

[0027] S5: Continue to add 0.3 parts of sodium polycarboxylate surfactant to the stirring tank and perform low-speed dispersion. The stirring tank rotates at 200 rpm for 10 min.

[0028] S6: After the stirring, the coating slurry is subjected to a demagnetization test and meets the requirements for post-coating. The setting parameters of the micro-gravure coating equipment are as follows: micro-gravure roller line number 120LPI, depth 90u, bevel angle 45°, diameter 100mm, coating machine micro-gravure roller speed ratio 1.0, speed 80m / min, coating machine oven temperature from the first section to the fifth section are 60℃ / 65℃ / 70℃ / 65℃ / 60℃ respectively, coating machine unwinding tension 30N, coating tension 40N, oven section tension 30N, winding tension 8N, winding into a semi-finished film;

[0029] S7: The semi-finished film is passed through a slitting machine, the speed of the slitting machine is controlled to be 120 m / min, the unwinding tension is 30 N, the winding tension is 15 N, and the winding taper is gradually reduced by 10%, and finally a finished diaphragm is obtained.

[0030] The beneficial effects of the present invention are:

[0031] 1. The present invention adds PPS fiber, inorganic ceramic powder and PI polymer to the fiber polymer slurry for coating, and coats the surface of the polyolefin diaphragm by micro-gravure transfer method. The network structure of the PPS fiber and the inorganic ceramic powder are used to form a dense coating. The PI polymer forms a bond between the coating and the polyolefin diaphragm, which is beneficial to the lyophilicity and liquid retention of the high-temperature diaphragm resistant to electrolyte immersion coating, while improving the heat resistance and corrosion resistance of the diaphragm, thereby ensuring the working safety performance of the battery.

[0032] 2. The solvent used in the high temperature resistant fiber polymer slurry of the present invention is ultrapure water with a conductivity of usually 0.055-0.1 μS / cm. Through the preparation of the high temperature resistant fiber polymer slurry and micro gravure roller transfer coating, the coating thickness is controlled to be 2-4 μm, and the coating surface density is controlled to be 3-8 g / m 2 The width of the semi-finished film is 0.5-1.5m. According to the thickness classification, it can not only be applied to existing conventional liquid lithium-ion battery isolation membrane materials, but also can be applied to solid-state batteries by utilizing its good electrical conductivity and ion channels.

[0033] 3. The present invention coats a fiber polymer on the basis of a polyolefin diaphragm, which can not only improve the high temperature resistance of the diaphragm, but also improve the stability of the coating when the diaphragm is immersed in an organic solvent of an electrolyte. It can not only maintain the stability of the diaphragm during the baking stage of the battery cell to prevent the electrode from leaking black, but also improve the adhesion between the coating and the electrode after the battery cell is injected with liquid to prevent the battery cell from becoming fluffy, causing thermal runaway and resulting in bulging, thereby greatly improving the safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION

[0035] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with examples. The examples are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0036] Example 1

[0037] A high temperature resistant diaphragm coated with electrolyte immersion comprises a diaphragm substrate and a diaphragm coating, wherein the diaphragm coating is formed by coating a high temperature resistant fiber polymer slurry, wherein the high temperature resistant fiber polymer slurry comprises the following components by mass: 3.2 parts of PPS fiber, 12 parts of PI polymer, 73 parts of aluminum oxide, 6.2 parts of CMC thickener, 5.3 parts of acrylic resin glue, and 0.3 parts of sodium polycarboxylate surfactant. The high temperature resistant fiber polymer slurry also comprises a solvent, which is ultrapure water, 185 parts of ultrapure water, and in the liquid proportion of the finished slurry, ultrapure water accounts for 64.9%. The solid content of the slurry in the diaphragm coating is 35.1%, and the solvent used in the slurry is ultrapure water, and the conductivity is generally 0.055-0.1 μS / cm.

[0038] The specific preparation method is as follows: first, deionized ultrapure water, CMC thickener, inorganic ceramic powder, and PPS fiber are preliminarily premixed and dispersed, the operation time of the stirring tank is 120 minutes, the stirring revolution is 25 rpm, and the rotation is 1800 rm. The fully premixed slurry is subjected to high-speed grinding and shearing, wherein the grinding speed is 800 rpm, and the pump speed of the grinder is 1 s / time. The ground solution enters the stirring tank and reaches the required solution particle size; PI polymer is added to the ground solution for high-speed mixing, the high-speed dispersed stirring tank revolves 30 rpm, rotates 2800 rpm, and the stirring time is 60 minutes; acrylic resin glue is added to continue low-speed mixing, the low-speed dispersed stirring tank rotates 200 rpm, and the stirring time is 30 minutes; polycarboxylic acid sodium salt surfactant is added for low-speed mixing, the low-speed dispersed stirring tank rotates 200 rpm, and the stirring time is 10 minutes to form a coating slurry;

[0039] After stirring, the coating slurry is subjected to demagnetization test and then coated. The micro-gravure roller line number is 120LPI, the depth is 90u, the bevel angle is 45°, and the diameter is 100mm; the micro-gravure roller speed ratio of the coating machine is 1.0, and the speed is 80m / min; the oven temperature of the coating machine is 55℃ / 60℃ / 67℃ / 60℃ / 55℃ from the first section to the fifth section respectively; the unwinding tension of the coating machine is 30N, the coating tension is 40N, the oven section tension is 30N, and the winding tension is 8N, and the semi-finished film is wound;

[0040] The semi-finished film is passed through a secondary slitting device and cut into the required width as required; specifically, the semi-finished film is passed through a primary slitting machine; the speed of the slitting machine is controlled to be 120m / min, the unwinding tension is 30N, the winding tension is 15N, and the winding taper is gradually reduced by 10%, and finally a finished diaphragm is obtained.

[0041] Example 2

[0042] A high temperature resistant diaphragm coated with electrolyte immersion comprises a diaphragm substrate and a diaphragm coating, wherein the diaphragm coating is formed by coating a high temperature resistant fiber polymer slurry, wherein the high temperature resistant fiber polymer slurry comprises the following components by mass: 4.5 parts of PPS fiber, 14 parts of PI polymer, 69.6 parts of boehmite, 5.8 parts of CMC thickener, 5.7 parts of acrylic resin glue, and 0.4 parts of polycarboxylic acid sodium salt surfactant. The high temperature resistant fiber polymer slurry also comprises a solvent, which is ultrapure water. In the liquid proportion of the finished slurry, ultrapure water accounts for 60%, the solid content of the slurry in the diaphragm coating is 40%, and the solvent used in the slurry is ultrapure water, and the conductivity is generally 0.055-0.1 μS / cm.

[0043] The specific preparation method is as follows: first, deionized ultrapure water, CMC thickener, inorganic ceramic powder, and PPS fiber are preliminarily premixed and dispersed, the operation time of the stirring tank is 180 minutes, the stirring revolution is 28 rpm, and the rotation is 2000 rm. The fully premixed slurry is subjected to high-speed grinding and shearing, wherein the grinding speed is 900 rpm, and the pump speed of the grinder is 1s / time. The ground solution enters the stirring tank and reaches the required solution particle size; PI polymer is added to the ground solution for high-speed mixing, the high-speed dispersed stirring tank revolves 32 rpm, rotates 2850 rpm, and the stirring time is 100 minutes; acrylic resin glue is added to continue low-speed mixing, the low-speed dispersed stirring tank rotates 240 rpm, and the stirring time is 40 minutes; polycarboxylic acid sodium salt surfactant is added for low-speed mixing, the low-speed dispersed stirring tank rotates 240 rpm, and the stirring time is 15 minutes to form a coating slurry;

[0044] After stirring, the coating slurry is subjected to demagnetization test and then coated. The micro-gravure roller line number is 120LPI, the depth is 90u, the bevel angle is 45°, and the diameter is 100mm; the micro-gravure roller speed ratio of the coating machine is 1.0, and the speed is 80m / min; the oven temperature of the coating machine is 65℃ / 70℃ / 75℃ / 70℃ / 65℃ from the first section to the fifth section respectively; the unwinding tension of the coating machine is 30N, the coating tension is 40N, the oven section tension is 30N, and the winding tension is 8N, and the semi-finished film is wound;

[0045] The semi-finished film is passed through a secondary slitting device and cut into the required width as required; specifically: the semi-finished film is passed through a primary slitting machine; the slitting machine speed is controlled at 110m / min, the unwinding tension is 32N, the winding tension is 14N, and the winding taper is gradually reduced at a rate of 12% to obtain a finished diaphragm.

[0046] Example 3

[0047] A high temperature resistant diaphragm coated with electrolyte immersion includes a diaphragm substrate and a diaphragm coating, wherein the diaphragm coating is formed by coating a high temperature resistant fiber polymer slurry, wherein the high temperature resistant fiber polymer slurry includes the following components by mass: 4.8 parts of PPS fiber, 14.5 parts of PI polymer, 68 parts of aluminum oxide, 7 parts of CMC thickener, 5.5 parts of acrylic resin glue, and 0.2 parts of polycarboxylic acid sodium salt surfactant. The high temperature resistant fiber polymer slurry also includes a solvent, which is ultrapure water. In the liquid ratio of the finished slurry, ultrapure water accounts for 62%, the solid content of the slurry in the diaphragm coating is 38%, and the solvent used in the slurry is ultrapure water, and the conductivity is usually 0.055-0.1μS / cm.

[0048] The specific preparation method is as follows: first, deionized ultrapure water, CMC thickener, inorganic ceramic powder, and PPS fiber are preliminarily premixed and dispersed, the operation time of the stirring tank is 200 minutes, the stirring revolution is 34 rpm, and the rotation is 2950 rpm. The fully premixed slurry is subjected to high-speed grinding and shearing, wherein the grinding speed is 820 rpm, and the pump speed of the grinder is 1 s / time. The ground solution enters the stirring tank and reaches the required solution particle size; PI polymer is added to the ground solution for high-speed mixing, the high-speed dispersed stirring tank revolves at 36 rpm, rotates at 2950 rpm, and the stirring time is 100 minutes; acrylic resin glue is added to continue low-speed mixing, the low-speed dispersed stirring tank rotates at 280 rpm, and the stirring time is 50 minutes; polycarboxylic acid sodium salt surfactant is added for low-speed mixing, the low-speed dispersed stirring tank rotates at 280 rpm, and the stirring time is 20 minutes to form a coating slurry;

[0049] After stirring, the coating slurry is subjected to demagnetization test and then coated. The micro-gravure roller line number is 120LPI, the depth is 90u, the bevel angle is 45°, and the diameter is 100mm; the micro-gravure roller speed ratio of the coating machine is 1.0, and the speed is 80m / min; the oven temperature of the coating machine is 65℃ / 70℃ / 75℃ / 70℃ / 65℃ from the first section to the fifth section respectively; the unwinding tension of the coating machine is 30N, the coating tension is 40N, the oven section tension is 30N, and the winding tension is 8N, and the semi-finished film is wound;

[0050] The semi-finished film is passed through a secondary slitting device and cut into the required width as required; specifically, the semi-finished film is passed through a primary slitting machine; the speed of the slitting machine is controlled to be 100m / min, the unwinding tension is 34N, the winding tension is 13N, and the winding taper is gradually reduced at a ratio of 14% to obtain a finished diaphragm.

[0051] The invention prepares an electrolyte-resistant high-temperature resistant diaphragm with an equal thickness of 16um and a polyolefin substrate of 12um, and transfer-coats the double-sided coating of the base film with 2um each by a micro-gravure roller. The finished product after winding is sampled with a length of 100mm and a width of 100mm, and is marked with lines in the length and width directions. The actual length direction M1 and the actual width direction T1 before baking are tested, and the oven is set at 200°C for 20 minutes. The length M2 and the width T2 are marked after baking, and the shrinkage is defined according to the shrinkage values ​​before and after baking. The shrinkage rate in the length direction is (M1-M2) / M1. The sample length of the finished product after synchronous sampling and winding is 100mm and the width is 100mm. It is placed in lithium hexafluorophosphate electrolyte at room temperature for 48 hours. The weight of the diaphragm is tested before immersion G1. After immersion, it is rinsed with clean water and then dried in an oven at 60℃ and weighed G2. The integrity is verified according to the weight loss ratio before and after electrolyte immersion. The integrity ratio is (G1-G2) / G1. The shrinkage test of the diaphragm and the integrity of the electrolyte immersion are shown in the following table.

[0052] project Thermal shrinkage%(200℃ / 20min) Electrolyte immersion integrity % (LFP Embodiment 1 2.37 92.27 Embodiment 2 2.06 93.89 Embodiment 3 1.72 96.14

[0053] It can be seen that a preparation method of a high-temperature resistant diaphragm coated with electrolyte immersion is proposed, which can better improve the heat resistance of the diaphragm and the interface integrity of the diaphragm after battery injection, and better ensure battery safety.

[0054] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A high temperature resistant diaphragm coated with electrolyte immersion resistance, characterized in that: It includes a diaphragm base and a diaphragm coating, wherein the diaphragm coating is coated with a high-temperature resistant fiber polymer slurry, and the high-temperature resistant fiber polymer slurry includes the following components by mass: 2-5 parts of PPS fiber, 8-15 parts of PI polymer, 65-80 parts of inorganic ceramic powder, 4-8 parts of CMC thickener, 3-6 parts of acrylic resin glue, and 0.1-0.5 parts of polycarboxylic acid sodium salt surfactant. The high-temperature resistant fiber polymer slurry also includes a solvent, which is ultrapure water. The solid content of the slurry in the diaphragm coating is 32-45%.

2. The electrolyte immersion-resistant high temperature resistant diaphragm according to claim 1, characterized in that: The high temperature resistant fiber polymer slurry is transferred and coated on both sides of the diaphragm substrate by a micro-gravure roller.

3. The electrolyte immersion-resistant high temperature resistant diaphragm according to claim 1, characterized in that: The high temperature resistant fiber polymer slurry comprises the following components by mass: 4.8 parts of PPS fiber, 14.5 parts of PI polymer, 68 parts of inorganic ceramic powder, 7 parts of CMC thickener, 5.5 parts of acrylic resin glue, and 0.2 parts of polycarboxylic acid sodium salt surfactant.

4. The electrolyte immersion-resistant high temperature resistant diaphragm according to claim 1, characterized in that: The PPS fiber is a short fiber with a particle size of D50 less than 12 um, the PI polymer is a para- or meta-polyimide emulsion, and the inorganic ceramic powder is one of alumina and boehmite.

5. The method for preparing a high temperature resistant diaphragm resistant to electrolyte immersion coating according to any one of claims 1 to 4, characterized in that: The steps include: S1: CMC thickener, inorganic ceramic powder, PPS fiber and ultrapure water are pre-mixed and dispersed; S2: After premixing and dispersion, it is subjected to high-speed grinding and shearing to reach the required solution particle size; S3: adding PI polymer to the ground solution and mixing at high speed; S4: Add acrylic resin glue and continue mixing at low speed; S5: adding a polycarboxylate sodium salt surfactant and mixing at a low speed to form a coating slurry; S6: Transfer coating, drying and rolling into semi-finished products through micro-gravure coating equipment; S7: Cut the battery cells into finished products according to their size requirements using a slitting machine.

6. The method for preparing a high temperature resistant diaphragm resistant to electrolyte immersion coating according to claim 5, characterized in that: The solvent for preliminary premixing and dispersion in step S1 is ultrapure water, which is premixed and dispersed in a premixing tank, which has an orbital speed of 20-30 rpm and an autorotation speed of 1000-3000 rpm. In step S3, the stirring tank for high-speed dispersion has an orbital speed of 25-40 rpm and an autorotation speed of 2000-3000 rpm. In step S4, the autorotation speed of low-speed mixing is 100-300 rpm. In step S6, the drying temperature of the oven is 50-80° C., and the temperature is set in a gradient manner of low to high.

7. The method for preparing a high temperature resistant diaphragm resistant to electrolyte immersion coating according to claim 5, characterized in that: In step S7, the speed of the slitting machine is controlled to be 60-150 m / min, the unwinding tension of the slitting machine is 20-40 N, the winding tension is 10-20 N, and the winding taper is gradually reduced at a rate of 10%.

8. The method for preparing a high temperature resistant diaphragm resistant to electrolyte immersion coating according to claim 5, characterized in that: The coating thickness of the electrolyte-resistant high-temperature resistant diaphragm is controlled to be 2-4 um, and the coating surface density is controlled to be 3-8 g / m 2 , the width of semi-finished film is 0.5-1.5m.

9. The method for preparing a high temperature resistant diaphragm resistant to electrolyte immersion coating according to claim 5, characterized in that: The viscosity of the coating slurry in step S5 is 20-200 mps, and the particle size D50 is 0.5-2 um.

10. The method for preparing a high temperature resistant diaphragm resistant to electrolyte immersion coating according to claim 5, characterized in that: The specific steps are as follows: S1: Prepare 6.2 parts of CMC thickener, 73 parts of inorganic ceramic powder, 3.2 parts of PPS fiber, add 185 parts of ultrapure water according to the liquid content, add to the premixing tank, premix and disperse for 120 minutes, revolve at 25 rpm, and rotate at 1800 rpm; S2: The premixed and dispersed solution enters the grinding and shearing process through the pump speed, the grinding speed is 800rmp, the pump speed of the grinder is 1s / time, and the ground solution enters the stirring tank; S3: grind the solution into a stirring tank, add 12 parts of PI polymer, and perform high-speed dispersion. The stirring tank for high-speed dispersion revolves at 30 rpm and rotates at 2800 rpm for 60 min. S4: 5.3 parts of acrylic resin glue is added to the stirring tank and dispersed at a low speed. The stirring tank rotates at 200 rpm for 30 min. S5: Continue to add 0.3 parts of sodium polycarboxylate surfactant to the stirring tank and perform low-speed dispersion. The stirring tank rotates at 200 rpm for 10 min. S6: After the stirring, the coating slurry is subjected to a demagnetization test and meets the requirements for post-coating. The setting parameters of the micro-gravure coating equipment are as follows: micro-gravure roller line number 120LPI, depth 90u, bevel angle 45°, diameter 100mm, coating machine micro-gravure roller speed ratio 1.0, speed 80m / min, coating machine oven temperature from the first section to the fifth section are 60℃ / 65℃ / 70℃ / 65℃ / 60℃ respectively, coating machine unwinding tension 30N, coating tension 40N, oven section tension 30N, winding tension 8N, winding into a semi-finished film; S7: The semi-finished film is passed through a slitting machine, and the speed of the slitting machine is controlled to be 120m / min, the unwinding tension is 30N, the winding tension is 15N, and the winding taper is gradually reduced by 10%, and finally a finished diaphragm is obtained.

Citation Information

Patent Citations

  • Lithium ion battery diaphragm with polymer inorganic coating and preparation method for lithium ion battery diaphragm

    CN103618059A

  • Diaphragm and lithium ion battery containing diaphragm

    CN114142167A

  • Composite diaphragm, preparation method thereof and sodium ion battery

    CN115347325A

  • Lithium ion battery diaphragm, preparation method thereof and lithium ion battery

    CN115548576A

  • Separator and preparation method therefor and electrochemical device comprising separator

    WO2019157695A1